Case Report: Immune dysregulation associated with long-lasting regression of a (pre)leukemic clone - Koedijk, Joost B.; van Beek, Thomas B.; Vermeulen, Marijn A.; Kester, Lennart A.; Schweighart, Elizabeth K.; Nierkens, Stefan; Belderbos, Mirjam E.; Zwaan, C. Michel; Heitink-Pollé, Katja M. J.; Heidenreich, Olaf (Frontiers in Immunology, 2023)
Regression of leukemia in the absence of disease-modifying therapy remains poorly understood, although immunological mechanisms are thought to play a role. Here, we present a unique case of a 17-year-old boy with immune dysregulation and long-lasting regression of a (pre)leukemic clone in the absence of disease-modifying therapy. Using molecular and immunological analyses, we identified bone marrow features associated with disease control and loss thereof. In addition, our case reveals that detection of certain fusion genes with hardly any blasts in the bone marrow may be indicative of an accompanying oncogenic fusion gene, with implications for disease surveillance- and management in future patients.